Hiden Movement KH. Hasyim Asy’ari dalam Kajian Fiqih Siyasah - Muhammad Fahmi Hidayatullah (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2017)
The dynamics of the history of independence heroes become an important thing for us to look at together some of the historical literature of struggle, the role of the santri lost from the important fragment in history to make the author want to reveal the movement behind the scenes. The movement is known as isltilah hiden movement that represents the struggle of the santri based on fiqh siyasah. Ijtihâd political kyai based fiqih siyasah able to move all the elements from various circles both ideological and identity groups through the fatwa Resolution Jihad. But what we need to know is how the fatwa can be realized and what are the components of the hiden movement KH. Hasyim Asy’ari. The purpose of writing this scientific paper to describe the idea and action hiden movement KH. Hasyim Asy’ari is based on fiqih siyasah. While research methodology in writing using descriptive-qualitative literature.